2015
DOI: 10.1167/iovs.15-18058
|View full text |Cite
|
Sign up to set email alerts
|

Changes in Irregular Corneal Astigmatism With Age in Eyes With and Without Cataract Surgery

Abstract: In patients from 50 to 80 years of age who underwent cataract surgery, irregular corneal astigmatism, both the asymmetry and higher-order irregularity components, increased significantly with increasing age, whereas regular astigmatism induces an against-the-rule shift. The higher-order irregularity component persistently increased postoperatively, whereas the asymmetry component did not change significantly.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…The average age of our patients was 30.66 years, it is a very young age, within the framework of a study on the cataract surgery, or generally the average age revolves around 60 years. This is due to the fact that astigmatism reverses with age [6]. There is more direct astigmatism in young subjects, and reverse in older subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The average age of our patients was 30.66 years, it is a very young age, within the framework of a study on the cataract surgery, or generally the average age revolves around 60 years. This is due to the fact that astigmatism reverses with age [6]. There is more direct astigmatism in young subjects, and reverse in older subjects.…”
Section: Discussionmentioning
confidence: 99%
“…In order to reduce occurrence of SIA, the authors propose to make temporal incisions by MSICS [3] [4] [5]. Temporal incisions generate less SIA because of the distance of this site from the visual axis, and the eyelid blink tends to create a drag on the incision [4], but also because of the predominance of reverse (irregular) astigmatisms in the elderly [6] most affected by cataracts. In these patients with reverse astigmatism, SIA is opposed to preexisting astigmatism with a tendency to reduce the latter [7].…”
Section: Introductionmentioning
confidence: 99%
“…Our data suggested that ANTERION demonstrated superior repeatability for the measurement of J0, which represents with-the-rule and against-the-rule astigmatism, and its agreement with the IOLMaster500 was poor. In practice, it is important to perform corneal topography when before implanting a toric IOL in cataract surgery since irregular corneal astigmatism, which is not correctable by toric IOL, has been shown to increase with increasing age 28 . It is likely that the difference between PCI-based and swept-source OCT based devices exists because of the different methods used to analyze the mires of spots re ected from the cornea.…”
Section: Discussionmentioning
confidence: 99%
“…The assumption of orthogonality between steep and flat meridians in corneal power maps has been a common feature in the analysis of astigmatism and in clinical techniques to determine the eye's visual acuity, although possible meridional non-orthogonality has been identified earlier. 11,14,[32][33][34] Optical power nonorthogonality was acknowledged in the literature as a contributing factor to high-order aberrations and identified by indices that do not provide clinical parameters like refractive power or axis angle. Despite being expressed quantitatively and statistically by a normalized Fourier series coefficient called the irregularity index, no expression of non-orthogonal astigmatism magnitude or axis angle has been presented.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, the existing literature that evaluates corneal irregularity by Fourier series harmonic ignores the irregular astigmatism phase angle β 3 and does not associate it with a specific physical meaning. 11,14,15 While it is acknowledged that a quantitative degree of irregularity in refractive power exists in normal eyes and this knowledge has been simulated by mathematical modeling 16 , no technique is available to locate the axes of irregular astigmatism. As a result, irregular astigmatism cannot be fully corrected by existing spectacle lenses and a degree of astigmatism will remain after correction.…”
Section: Introductionmentioning
confidence: 99%